Mass absorption cross section of black carbon for Aethalometer in the Arctic - Singh, Mohit; Kondo, Yutaka; Ohata, Sho; Mori, Tatsuhiro; Oshima, Naga; Hyvärinen, Antti; Backman, John; Asmi, Eija; Servomaa, Henri; Schnaiter, Franz Martin; Andrews, Elisabeth; Sharma, Sangeeta; et al. (Taylor & Francis, 2024)
Long-term measurements of the mass concentration of black carbon (BC) in the atmosphere (MBC) with well-constrained accuracy are indispensable to quantify its emission, transport, and deposition. The aerosol light absorption coefficient (babs), usually measured by a filterbased absorption photometer, including an Aethalometer (AE), is often used to estimate MBC. The measured babs is converted to MBC by assuming a value for the mass absorption cross section (MAC). Previously, we derived the MAC for AE (MAC (AE)) from measured babs and independently measured MBC values at two sites in the Arctic. MBC was measured with a filter-based absorption photometer with a heated inlet (COSMOS). The accuracy of the COSMOS-derived MBC (MBC (COSMOS)) was within about 15%. Here, we obtained additional MAC (AE) measurements to improve understanding of its variability and uncertainty. We measured babs (AE) and MBC (COSMOS) at Alert (2018–2020), Barrow (2012–2022), NyÅlesund (2012–2019), and Pallas (2019–2022). At Pallas, we also obtained four-wavelength photoacoustic aerosol absorption spectrometer (PAAS-4k) measurements of babs. babs (AE) and MBC (COSMOS) were tightly correlated; the average MAC (AE) at the four sites was 11.4 ± 1.2m2 g−1 (mean ± 1r) at 590nm and 7.76 ± 0.73m2 g−1 at 880 nm. The spatial variability of MAC (AE) was about 11% (1r), and its year-to-year variability was about 18%. We compared MAC (AE) in the Arctic with values at mid-latitudes, measured by previous studies, and with values obtained by using other types of filter-based absorption photometer, and PAAS-4k.